Familial transmission of chromoanagenesis leads to unpredictable unbalanced rearrangements through meiotic recombination. Issue 4 (19th January 2023) - Masson, Julie; Pebrel‐Richard, Céline; Egloff, Matthieu; Frétigny, Mathilde; Beaumont, Marion; Uguen, Kevin; Rollat‐Farnier, Pierre‐Antoine; Diguet, Flavie; Perthus, Isabelle; Le Gudayer, Gwenaël; Haye, Damien; Dupeyron, Marie‐Noëlle Bonnet; et al.
Abstract: Chromoanagenesis is a cellular mechanism that leads to complex chromosomal rearrangements (CCR) during a single catastrophic event. It may result in loss and/or gain of genetic material and may be responsible for various phenotypes. These rearrangements are usually sporadic. However, some familial cases have been reported. Here, we studied six families in whom an asymptomatic or paucisymptomatic parent transmitted a CCR to its offspring in an unbalanced manner. The rearrangements were characterized by karyotyping, fluorescent in situ hybridization, chromosomal microarray (CMA) and/or whole genome sequencing (WGS) in the carrier parents and offspring. We then hypothesized meiosis‐pairing figures between normal and abnormal parental chromosomes that may have led to the formation of new unbalanced rearrangements through meiotic recombination. Our work indicates that chromoanagenesis might be associated with a normal phenotype and normal fertility, even in males, and that WGS may be the only way to identify these events when there is no imbalance. Subsequently, the CCR can be transmitted to the next generation in an unbalanced and unpredictable manner following meiotic recombination. Thereby, prenatal diagnosis using CMA should be proposed to these families to detect any pathogenic imbalances in the offspring. Abstract : We studied six families in whom an asymptomatic or paucisymptomatic mother or father transmitted a complex chromosomal rearrangement to its offspring in an unbalanced manner. Karyotyping, fluorescent in situ hybridization, chromosomal microarray and/or whole genome sequencing (WGS) were performed to characterize the rearrangements and to hypothesize meiosis‐pairing figures that may have led to the formation of new unbalanced rearrangements through meiotic recombination.